2015
DOI: 10.2458/azu_rc.57.18404
|View full text |Cite
|
Sign up to set email alerts
|

Marine Reservoir Corrections on the Southeastern Coast of Brazil: Paired Samples from the Saquarema Shellmound

Abstract: The Saquarema archaeological site, on the Atlantic coast of the Rio de Janeiro State, is one of many shellmounds built on the Brazilian coast by hunter-gatherer populations during the Holocene. We used archaeological material from this site with the aim of evaluating the marine reservoir effect (MRE) in the region. Radiocarbon ages of 45 marine and 6 terrestrial samples from this shellmound provided data for assessing the MRE and the influences of freshwater and seasonal coastal marine upwelling in this specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
4
27
0
3
Order By: Relevance
“…The groundfish catches were the result of multi-gear strategies in seasonal fisheries. Radiometric age, geochemical analyses and climate reconstruction of these ichthyoarchaeological remains [ 52 , 53 , 54 , 55 ] were used to supporting our findings.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The groundfish catches were the result of multi-gear strategies in seasonal fisheries. Radiometric age, geochemical analyses and climate reconstruction of these ichthyoarchaeological remains [ 52 , 53 , 54 , 55 ] were used to supporting our findings.…”
Section: Introductionmentioning
confidence: 68%
“…Data analyses were carried out on LACAMS software developed at the Physics Institute of Universidade Federal Fluminense [ 98 ]. Calibration of otolith radiocarbon dates was performed with OxCal software v 4.2.3 from the Oxford University [ 99 ], using the Marine13 curve [ 100 ] in the 2-sigma range with an offset for local marine reservoir corrections (ΔR 14 C years) according to the following shellmound localities: Saquarema [ 53 ], Manitiba [ 55 ] and Southeastern Brazil [ 101 ]. Cross-comparisons were conducted in the Beta Analytic Inc. laboratory, following standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Chronological assumptions based on disturbed archaeostratigraphic layering, mainly in shellmounds with less than about 2 m in depth, can lead to serious mistakes. Alves et al (2015b), working on MRE in a southeastern Brazilian shellmound, have shown that samples originating from different depths in the site exhibited statistically-indistinguishable ages.…”
Section: Introductionmentioning
confidence: 97%
“…Russell et al (2010) have proposed a statistical approach that takes into account a large number of samples from the same context and different combinations of marineeterrestrial pairs. Another possibility is the use of phase models in the OxCal software, where groups of samples from the same archaeological layers, for example, can be related to each other (Bronk Ramsey and Lee, 2013;Faivre et al, 2015;Alves et al, 2015b;Carvalho et al, 2015;Macario et al, 2015a). Provided that terrestrial samples are calibrated with the atmospheric curve and marine samples with the marine curve, the offset DR can be adjusted to maximize the contemporaneity of the calibrated results.…”
Section: Introductionmentioning
confidence: 98%
“…Na região de Saquarema (22° 55′ 12″ S, 42° 30′ 36″ W), outros dois sítios foram estudados: os sambaquis de Manitiba (carvões, moluscos marinhos e terrestres) e Saquarema (moluscos marinhos, otólitos e carvões). Para esses sítios foram obtidos os valores de ∆R=-82 ± 71 anos de 14 C e -140 ± 66 anos de 14 C (Alves et al 2015b), respectivamente. Mais recentemente, Macario et al (2016) realizaram novo estudo no Sambaqui de Usiminas, na Ilha de Cabo Frio, desta vez comparando um grande número de moluscos marinhos e terrestres.…”
Section: O Efeito De Reservatório Marinho Na Costa Do Brasilunclassified